2013
DOI: 10.17659/01.2013.0080
|View full text |Cite
|
Sign up to set email alerts
|

Modified Cantwell-Ransley Repair of Male Penopubic Epispadias: Report of Two Cases and Review of the Literature

Abstract: Abstract:The reported incidence of male epispadias is 1 in 1,17,000 male births. The majority of cases go unseen in surgeons' life because of uncommon existence of this anomaly. We present our experience using the modified Cantwell-Ransley technique; particularly focusing on postoperative anatomical and functional outcomes. Between 2011 and 2013, two boys having primary penopubic epispadias with the spraying of urinary stream underwent one stage surgical reconstruction. Cavernocavernostomy was performed in all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…[14] In our series, no patient developed fistula or stricture (although our series comprises of five cases only) similar to findings of Pippi Salle et al [18] In the report of two cases of epispadias repair by modified Cantwell-Ransley by Lodh et al, there is no fistula or need for any dilatation post-operatively. [4] Only one patient had superficial infection of dorsal penile skin which healed by secondary intention and did not require a secondary procedure in our series. In series of Nerli et al of 43 cases treated by similar technique found dorsal skin infection or incision separation in three children and none required a secondary procedure in his series.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…[14] In our series, no patient developed fistula or stricture (although our series comprises of five cases only) similar to findings of Pippi Salle et al [18] In the report of two cases of epispadias repair by modified Cantwell-Ransley by Lodh et al, there is no fistula or need for any dilatation post-operatively. [4] Only one patient had superficial infection of dorsal penile skin which healed by secondary intention and did not require a secondary procedure in our series. In series of Nerli et al of 43 cases treated by similar technique found dorsal skin infection or incision separation in three children and none required a secondary procedure in his series.…”
Section: Discussionmentioning
confidence: 69%
“…[7] Several surgical procedures have been described till date but treatment for this anomaly is far from trival and repair can be challenging. [4] The goal of surgery is to achieve functionally and cosmetically acceptable penis. [8] The first description of epispadias repair is by Cantwell in 1895 till then techniques evolved through various modification.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations